THE ROLE OF EMOTIONAL INTELLIGENCE AND POSITIVE PSYCHOLOGY IN WORKPLACE PERFORMANCE AND LEADERSHIP (CAHIERS MAGELLANES-NS, 2024)
The paper explores the interconnected roles of Emotional Intelligence (EI) and Positive Psychology in enhancing workplace performance and leadership effectiveness. Emotional Intelligence, defined as the ability to recognize, understand, and manage one's own emotions and the emotions of others, has been increasingly acknowledged as a crucial factor in leadership success. Positive Psychology, focusing on strengths, virtues, and factors that contribute to human flourishing, complements EI by fostering an environment conducive to positive organizational outcomes. This paper synthesizes existing research to examine how these two constructs contribute to improved job performance, employee satisfaction, and leadership efficacy.The paper highlights key theoretical frameworks and empirical studies that demonstrate the impact of EI on various aspects of workplace dynamics, including conflict resolution, team collaboration, and stress management. It also delves into the principles of Positive Psychology, such as resilience, optimism, and strengths-based development, and their application in organizational settings. The integration of EI and Positive Psychology is shown to enhance leaders' ability to motivate and inspire their teams, create a supportive and positive work culture, and navigate the complexities of modern organizational life.Moreover, the paper discusses practical strategies for cultivating EI and Positive Psychology within organizations, such as targeted training programs, leadership development initiatives, and organizational policies that promote well-being and emotional awareness. The findings suggest that organizations that invest in these areas are likely to see significant improvements in employee engagement, productivity, and overall organizational performance. The review concludes with implications for future research and practice, emphasizing the need for a holistic approach to leadership development that incorporates both emotional and psychological dimensions.